2006
DOI: 10.1111/j.1468-2850.2006.00004.x
|View full text |Cite
|
Sign up to set email alerts
|

Examining Psychotherapy Processes in a Services Research Context.

Abstract: Interdisciplinary research efforts integrating services and interventions research methodologies are needed to improve the "real-world" clinical utility and impact of youth mental health research. "Hybrid" services and interventions research efforts can capitalize on the methodologic strengths of each research tradition in order to more rigorously examine and affect therapy processes in usual care youth mental health service settings. The goals of this article are to (a) identify the need for hybrid practice r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
90
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(91 citation statements)
references
References 101 publications
(145 reference statements)
1
90
0
Order By: Relevance
“…Shirk and Russell (1996) propose more research should focus on common patterns of interactions as they relate to change, given their robust correlation with positive outcomes in therapy regardless of theoretical approach. As most community based care providers describe an eclectic approach to their work with children and families, and ascribe greater importance to the alliance in their work than to specific techniques, why does most intervention research focus on the effectiveness of specific techniques rather than more common therapy processes relied upon in community work (Garland et al 2006)?…”
Section: Discussionmentioning
confidence: 98%
“…Shirk and Russell (1996) propose more research should focus on common patterns of interactions as they relate to change, given their robust correlation with positive outcomes in therapy regardless of theoretical approach. As most community based care providers describe an eclectic approach to their work with children and families, and ascribe greater importance to the alliance in their work than to specific techniques, why does most intervention research focus on the effectiveness of specific techniques rather than more common therapy processes relied upon in community work (Garland et al 2006)?…”
Section: Discussionmentioning
confidence: 98%
“…It is difficult to know how representative this is of their actual practices. Practical limitations prevented the use of role-plays or taped therapy sessions which would provide objective measures of practitioner behavior (Garland et al 2006). Previous research has shown that practitioners can reliably report their behavior in sessions when provided with structured and session-specific checklists (Carroll et al 1998).…”
Section: Limitationsmentioning
confidence: 99%
“…The PRAC project, which provided the structure and support for the research-practice partnership effort reported here, is a federally funded research study designed to characterize ''usual care'' communitybased out-patient psychotherapy for children ages 4-13 years with disruptive behavior problems and to examine the consistencies and inconsistencies between common practices in the community and evidencebased principles of care for this patient population (Garland et al, 2006). The research design requires videotaping of psychotherapy sessions among clinicians from multiple mental health disciplines, providing care to approximately 250 children and their families.…”
Section: Practice and Research: Advancing Collaboration (Prac) Projectmentioning
confidence: 99%
“…Details of the goals and structure of the partnership process are provided below, but in sum, this collaborative partnership was initiated to support a federally funded research project designed to characterize youth psychotherapy in publicly funded out-patient clinics, and to examine the consistency between community-based care and principles of evidence-based care (Garland, Hurlburt & Hawley, 2006). The research project is titled, ''Practice and Research: Advancing Collaboration'' (PRAC).…”
Section: Introductionmentioning
confidence: 99%